EVALUASI KESESUAIAN LAHAN DAN KELAYAKAN EKONOMI TANAMAN KEDELAI DI KECAMATAN WONOMULYO KABUPATEN POLEWALI MANDAR - Dirhana Purnama; Amir Tjoneng; Suriyanti Suriyanti (Percetakan Umi Toaha Makassar, 2022)
This research was conducted with the aims of: 1) evaluating the level of land suitability for soybean plants in Wonomulyo District, Polewali Mandar Regency; 2) Analyzing the limiting factors and land improvement actions that can be taken for soybean plants; and 3) Analyzing the economic feasibility of developing soybeans in Wonomulyo, Polewali Mandar District. This research was conducted in the Wonomulyo District, Polewali Mandar Regency. The study was conducted from March to April 2021. Primary data was obtained from interviews using questionnaires, direct observations, and documentation. Secondary data is data obtained from relevant agencies that can support research data. The data analysis used is soil sample analysis and economic analysis (R/C and B/C ratio). The results showed that: 1) the soybean land suitability class was classified as S2wrn class (quite suitable) covering observation points 1 to 6; 2) the main limiting factors are the availability of water (rainfall) and available nutrients (N-total and K2O); and 3) based on the income comparison, the income of soybean farmers is greater than the income equivalent to rice (Rp. 2.359.981 > Rp. 1.109.333). Based on per capita income, soybean farmers' income is lower than the income per capita of West Sulawesi Province (Rp. 2.359.981< Rp. 2.799.167).